A Feasibility Study on the Establishment of Meraki Footwear in Victory Mall, Caloocan City, Metro Manila (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
MERAKI FOOTWEAR is a proposed business that offers handmade shoes whose air soles are made of old airplane wheels. The researchers utilized survey method and library research to collect data and information. They formulated 10 questions that focus on the acceptability of product, price, place and promotion to one hundred (100)respondents in Rizal Ave. Ext. Caloocan, Metro Manila. MERAKI FOOTWEAR has 75% potential customers whose ages range from12 to 17 years old and 85% of the respondents were students. The proposed business location is rated accessible by the respondents and it is suited to the kind of business because the area is crowded. Majority of the respondents were found to buy shoes semi-annually and they look for good quality at cheaper price. They prefer local brands over international brands that gives the business better chance to be patronized. When asked about the material to be used for the shoes, they responded affirmation with those that are made out of airplane tire which is commonly called “Airsole”. Since the business is a general partnership, each of the partners will share 600,000 pesos to raise an initial capital of 3,000,000.00. The result of the general assumption revealed sales increase of 20% yearly. The Return on Investment is achievable on the first year of the business operation. The result of the research showed the capability and acceptability of the business and a great chance to be established in fields and in good running footwear industry because of its uniqueness.
Keywords: meraki footwear, feasibility study